Status Tanah Hak Erfpacht Yang Diperjualbelikan - Tuanaya, Firda Hawa; Laturette, Adonia Ivonne; Uktolseja, Novyta (Faculty of Law Universitas Pattimura, 2024)
Land ownership rights in Indonesia are very diverse, one of which is erfpacht rights. Erfpacht rights are rights to foreign land that have been in effect in Indonesia since colonial times, and were later changed to business use rights and building use rights. In accordance with the law, erfpacht land cannot be transferred to heirs or other parties. After the erfpacht right holder dies, the right to the land ends and the rights are returned to the state. Because, only the right holder has the authority to convert the land, and it cannot be converted by anyone else. So based on the problems above, this research will discuss whether the status of erfpacht land rights that have expired can be traded to other parties, as well as what are the legal consequences of the status of erfpacht land rights being traded. This legal research uses a normative juridical approach using primary, secondary and tertiary legal materials. Collection of legal materials is carried out through literature study and processing. Analysis of legal materials was carried out using a descriptive method using a qualitative approach. Based on the research results, it was concluded that erfpacht rights could be transferred (sold) to other parties and could be subject to mortgage (used as collateral to obtain loans from banks). Erfpacht rights can also be returned to the state, and can be revoked if they do not fulfill the conditions set out in the agreement.